AB1242 Role of sonography in the painful shoulder: Analysis of a rheumatological unit cohort of patients. (23rd January 2014) - Delle Sedie, A.; Carli, L.; Sardano, E.; Cioffi, E.; Bombardieri, S.; Riente, L.
Abstract : Background: Ultrasound (US) emerged as a key diagnostic tool for rheumatologists in the last two decades. It improves clinical diagnosis as well as follow-up of arthritis patients. It is well known the utility of US in the diagnostic assessment of shoulder pain. Objectives: To evaluate the shoulder findings by musculoskeletal US in the assessment of patients presenting with shoulder pain. Methods: We examined 209 patients (M:F=60:149), mean age 60±14 years (range 25-82 years), 55.5% of them affected by rheumatologic disorders (24 with rheumatoid arthritis, 12 with polimyalgia rheumatica, 7 with psoriatic arthritis, 4 with undifferentiated spondyloarthritis, 11 with fibromyalgia, 5 with systemic sclerosis, 5 with systemic lupus erythematosus). The other 48 patients complained shoulder pain with no established diagnosis. Ninety per cent of the patients had yet been treated with non steroidal antinflammatory drugs and/or analgesics without efficacy while 40% experienced partial remission by rehabilitative therapy. US examinations were performed with a Logiq9 machine (General Electrics Medical Systems, Milwaukee, WI) using a linear probe at a frequency of 10 MHz. We examined: tendon of the long head of biceps (LHB) muscle, supraspinatus, subscapularis and infraspinatus tendons, subacromiondeltoid and subscapolaris bursae, gleno-humeral and acromion-clavicular (AC) joints. We studied homogeneity, thickness and continuity of fibers of tendons, as well as the presence of effusion into the bursae and the joints. Finally we focused the attention on the cortical bone appearance. Results: Ninety-four patients (45%) showed tears of rotator cuff tendons usually localized in the supraspinatus tendon (69% of them were ≥65 years old), while long biceps tendon tear was present only in 14 cases (associated to supraspinatus tear). Effusion in the AC joint was observed in 29 patients (in 22 of them it was associated with rotator cuff tendon tear), while tenosynovitis of LHB tendon was shown in 133 patients (in 53 of them it was the only pathologic finding). Hyperechoic spots or linear aggregates were imaged in 56.4% of the patients. Tendinosis was more evident in the supraspinatus tendon (112 cases) while in other tendons only in 14-19% of subjects. Conclusions: US examination showed high prevalence of abnormal findings in painful shoulders, most of all in the ≥65 years old patients. US provide great help for the clinician for the screening of the painful shoulder, suggesting the need of an MRI in some cases, guiding invasive maneuvers (i.e. arthrocentesis or intrarticular injection) or, finally, in the follow-up. Disclosure of Interest: None Declared